Acute renal damage after using percutaneous coronariography: related risk factors - Alberto Hernández González; Caridad de Dios Soler Morejón; Teddy Osmin Tamargo Barbeito (Centro Provincial de Información de Ciencias Médicas, 2017)
Introduction: Acute renal damage provoked due to the use of contrast means is a complication that is often underestimated from the clinical point of view.  In general, there are low rates of presumption and diagnosis and it is associated with diagnostic and therapeutic interventions, as the percutaneous coronariography. Objective: To evaluate risk factors related to the emergence of nephropathy in patients that received percutaneous coronariography. Methods: A descriptive and analytic study of 37 patients that required percutaneous coronariography was carried out in theCardiologyCenter of "Carlos J. Finlay"Clinical-SurgicalHospital inHavana, from October, 2009 to January, 2010.  Three risk groups (low, medium or high) were conformed for that purpose according to the number of present factors, and all the members were treated with physiologic saline solution to 1 mL/kg/h.  The existence of acute renal damage was determined if a 25% increment or more of seric creatinin took place at 72 hours of having practiced the procedure, in comparison with the figures obtained initially. Results: Nephropathy was just induced in 4 patients (10.8%), 3 of which belonged to the high risk group.  There was no affectation in the members of the low risk group. Conclusions: The results of this study suggested the presence of risk factors that condition the emergence of a nephropathy after using percutaneous coronariography, mainly if two or more converge in the same patient.